Furrows. Undermining the Limits of Our Language (diségno, 2025)
In the following note –without delving into the broader topic of drawing as language, or seeking to establish the connections between verbal and graphic forms of communication– I take the opportunity to organize some reflections that have emerged over recent decades. These reflections have shown a certain practical effectiveness in educational and didactic contexts, and are based on references that are not particularly recent, yet far from obsolete. [read more]